Diet and food preference of the waterbuck (Kobus ellipsiprymnus defassa) in the Pendjari National Park- Benin - Kassa, Barthelemy; Libois, Roland; SINSIN, Brice (My University, 2008)
This study investigated composition and selectivity in diet for waterbuck in the Pendjari National Park in north-western Benin, through the use of micrographic analysis of faecal samples. Three plant species (Panicum anabaptistum, Echinochloa stagnina and Andropogon gayanus) were regularly consumed all year round. Meanwhile, three other species (i.e., Hyparrhenia involucrata, Acroceras amplectens and Oryza barthii) are mostly found in its diet during the beginning of the rainy season. During the dry season, long life grasses (>40%) and tree forage (about 35%) were the most dominant life form in the diet. On the contrary at the beginning of the rainy season, annual species (> 50%) were dominant. In conclusion, the waterbuck has a grazer regime when plant species are abundant and a mixed diet during the dry season.Waterbuck’s food niche breath, deﬁned by Hespenheide [Ecology and Evolution of communities. Harvard Univ. Press, 1975], was lower than 1, implying this antelope does not eat all food categories in a proportional way. Shannon diversity index showed that the diet was more diversiﬁed during the rainy season and less diversiﬁed at the end of the dry season. Based on [Ecology, 64 (1983), 1297] diet selectivity index, waterbuck exerted a positive selection on the major graminaceous species.
Keywords: Bénin; food; Pendjari Park; selectivity; water-buck